Measurement of the properties of a Higgs boson in the four-lepton final state - KAYA, MİTHAT (My University, 2014)
The properties of a Higgs boson candidate are measured in the H→ZZ→4 decay channel, with =e, μ, using data from pp collisions corresponding to an integrated luminosity of 5.1fb-1 at the center-of-mass energy of s=7TeV and 19.7fb-1 at s=8TeV, recorded with the CMS detector at the LHC. The new boson is observed as a narrow resonance with a local significance of 6.8 standard deviations, a measured mass of 125.6±0.4(stat)±0. 2(syst)GeV, and a total width ≤3.4GeV at the 95% confidence level. The production cross section of the new boson times its branching fraction to four leptons is measured to be 0.93-0.23+0.26(stat)-0.09+0.13(syst) times that predicted by the standard model. Its spin-parity properties are found to be consistent with the expectations for the standard-model Higgs boson. The hypotheses of a pseudoscalar and all tested spin-1 boson hypotheses are excluded at the 99% confidence level or higher. All tested spin-2 boson hypotheses are excluded at the 95% confidence level or higher. © 2014 CERN, for the CMS Collaboration.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Physics; Astronomy and Astrophysics; Natural Sciences; Temel Bilimler (SCI); Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; FİZİK, NÜKLEER; Natural Sciences (SCI); SPACE SCIENCE; PHYSICS; ASTRONOMY & ASTROPHYSICS; PHYSICS, NUCLEAR; Nükleer ve Yüksek Enerji Fiziği; Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Nuclear and High Energy Physics; Physical Sciences; Physics and Astronomy (miscellaneous)